Overview Of Additional Issue Of Shares And Debt In The Process Of Value Appraisal Of Shares And Planning Of Additional Issue Parameters - Kozyr, Yuriy V. (Archives of Business Research, 2017)
The article contains a theoretical analysis of the impact of additional issue of shares on the value of the invested and stock capital. The present analysis encompasses aspects of redistribution of capital between the old and new shareholders, as well as valuation procedures in different situations, both in terms of the volume of additional issue of shares and of payment methods. The income approach is used in the value appraisal. The principal place under the income approach is given to the shareholder value added model (model SVA). This article may be useful in solving a number of practical problems related to the issues of restructuring of the company's capital. Investment analysts will find in this article a tool of benefit-sharing analysis of the capital structure changes between “old” and “new” company's shareholders and will be able to make a calculation of the parameters of the additional issue of shares.